Liquidity Risk Management through Capital Increase Policies: A Future Perspective in Iraqi Islamic Banks - Al Naamnah, Hasan; Ben Aissia, Dorsaf; Al Yasiri, Hayder Salih Mahdi (The Journal of Accounting and Management, 2025)
This study aims to explore how banks manage liquidity risks due to their impact on financial stability, specifically through the policy of capital increase, and to analyse the effect of such increases on the stability of banks. The sample consisted of a group of banks listed on the Iraq Stock Exchange from 2018 to 2023. An inductive financial statement analysis approach was used to determine whether banks succeeded in managing liquidity risks through capital increases. The study reached several key findings. There is a positive relationship between liquidity risks and capital increases, indicating that when banks increase their capital, they tend to increase the loans granted, which may lead to significant financial crises, pushing them to borrow from other sources. It was observed that increasing capital did not reduce liquidity risks, and banks did not succeed in managing these risks effectively. This also points to weaknesses in risk management systems, internal controls, and non-compliance with regulations issued by the Central Bank of Iraq.